The Develompment of Media Based on Adobe Flash Player in Training Basic Technique of Futsal - Windiartha, Abdy; Kristiyanto, Agus; Purnama, Sapta Kunta (Journal of Physical Education Health and Sport, 2017)
This research focused on the development of media in learning by using adobe flash player. This study was research and development form. This product contains material on futsal basic technique practice. Media development was using Adobe Flash CS6 Professional software. The materials presented were (1) Basic futsal technique (2) brief futsal (3) futsal rules (4) field size, line, goal and futsal ball. Based on the stages adapted from the development model of Borg and Gall then obtained the following results: Assessment and validation of the material experts showed that the medium of learning both with a mean value of 3.87. Assessment and validation of media experts showed that the medium of learning both with the average value 4. The results of small group trials showed very good result that is average 4.42. The results of large group trials showed excellent results with a mean of 4.55. In operational test and product effectiveness, pre test and post test of 2 groups were applied. The first group was given media influence, and the second group was control group. Operational test results pretest value was 73.92, so it was included in enough category, and the average posttest value was 58.25 that included in enough category. The effectiveness test showed that the interactive learning media had significant effectiveness with t-count value> t-table that was 123,922> 1,70329 and p-value (significance) 0.000 <0,05 meaning that the media was effective. As the final conclusion stated that the product proved effective. For the posttest average value of 58.25seconds was included in enough category. As the final conclusion, this product was proven effective.